Theory of Dynamic Interactions: Synthesis - Barceló, Gabriel (Transactions on Engineering and Computing Sciences, 2017)
In this text, we carry out a brief summary of the Theory of Dynamic Interactions developed by the author in the new book: New Paradigm in Physics. Certain keys are provided to better understand the dynamic hypotheses proposed, conclusions are drawn from the studies carried out and ideas for future development are proposed in this area. The author believes that with this new model proposed, the understanding of our observational universe will be facilitated, as well as that of the physical phenomena we notice. This paper is based on ideas and excerpts from other texts by the author or his team, which are mentioned in the references. Nevertheless, some paragraphs may not be duly referenced.